The Influence of Social Media on Public Opinion Formation in the Post-Truth Era - Azzahra, Adelia; Tekle, Kiflu Chekole (Journal of Political Innovation and Analysis, 2024)
This study examines the impact of social media on public opinion formation in the post-truth era, characterized by the spread of biased or inaccurate information. Social media platforms, while facilitating information dissemination, often contribute to the creation of echo chambers and filter bubbles, shaping political perceptions and influencing public discourse. Through a qualitative approach, this research investigates how misinformation and disinformation campaigns leverage social media to manipulate public opinion and the role of education and policy regulation in counteracting these effects. The findings provide insights into regulatory frameworks and digital literacy strategies needed to mitigate the adverse effects of social media on political opinion.